2023
DOI: 10.1177/14648849231170519
|View full text |Cite
|
Sign up to set email alerts
|

Digital journalism in Spain: Technological, sociopolitical and economic factors as drivers of media evolution

Abstract: Digital journalism has been a reality in Spain for nearly 30 years. In this time, the number of digital media outlets has steadily increased to become the most abundant type of media in the 2020s, ahead of print, radio and television. Based on a quantitative analysis of the authors’ own database of active digital media outlets ( n = 2726) and an examination of Spain’s technological, sociopolitical and economic development in recent decades, this article identifies several factors that have spurred the evolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The economic crisis of 2008 led to a loss of circulation and advertisement incomes. Other characteristics are that journalism in Spain tends to rather comment than inform while few journalists are members of journalism associations which is affecting their working conditions negatively [ 36 ]. Media ownership is concentrated to a few owners while outlets often have political affiliations or leanings.…”
Section: Methodsmentioning
confidence: 99%
“…The economic crisis of 2008 led to a loss of circulation and advertisement incomes. Other characteristics are that journalism in Spain tends to rather comment than inform while few journalists are members of journalism associations which is affecting their working conditions negatively [ 36 ]. Media ownership is concentrated to a few owners while outlets often have political affiliations or leanings.…”
Section: Methodsmentioning
confidence: 99%
“…Spain leads Europe in the quantity of digital-native brands within its media rankings. It is remarkable for the proliferation of digital-native brands such as El Confidencial and Eldiario.es, which not only compete with, but also occasionally surpass, traditional outlets in terms of influence and audience reach (Salaverría & Martínez-Costa, 2023). These trends are not limited to national platforms but extend to regional and local media, mostly privately owned, and frequently using co-official languages to engage local communities (Negreira-Rey et al, 2022).…”
Section: The Spanish Media Landscapementioning
confidence: 99%
“…Digital-native news media have become a sizeable part of many online news markets (Salaverría, 2016) and have thrived despite, or even as a result of, challenging circumstances (Salaverría, 2021;Salaverría and Martínez-Costa, 2023), populating the "media ecosystem" from the periphery to the epicenter (López-García, Silva-Rodríguez and Vázquez-Herrero, 2023; Vázquez-Herrero, Negreira-Rey and López-García, 2023), although legacy brands enjoy structural advantages (Nelson, 2020). Nichols et al (2018: 6) identified two "waves" of digital news start-ups: first, "ad-supported aggregators which bundled together news from multiple sources -often as part of a 'portal' model", which we have shown is still present in some countries; and second, digital-born news sites that "produce their own content".…”
Section: Introductionmentioning
confidence: 99%